Utilizing Canva as an Innovative Solution in Developing Digital Teaching Media in Schools - Pratama, Rendy Yudha; Bungsudi; Syaifurrohman, Amir; Kurnia, Ulfa Isni; Prasetiyo, Andri; Bastian, Arif Alexander; Gumay, Jovana Renaldy; Nuruhidin, Ahmad (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2025)
Background of the study:Most teachers in primary and secondary schools continue to rely on conventional teaching materials. A key issue is the limited knowledge and skills in using digital design tools such as Canva, which hinders their ability to create engaging and interactive teaching media.Purpose and scope of the paper:This community service program aims to enhance teachers’ digital literacy and creative capacity by introducing Canva as a practical and innovative tool for developing digital teaching media, specifically targeting educators in Pringsewu Regency.Methods:The program engaged 20 teachers from various disciplines. It employed a combination of workshops, hands-on training, guided tutorials, and evaluations. Data collection methods included pre- and post-training questionnaires, observations, and documentation of participants’ teaching media outputs.Results:Following the program, 95% of participants showed improved skills in using Canva. Additionally, more than 25 digital teaching products were created. Teachers also reported increased confidence and motivation in integrating digital media into their instructional practices.Conclusion:Canva proves to be an effective and accessible tool for enhancing teachers’ capabilities in designing digital teaching materials. With proper training and support, teachers can independently develop innovative teaching media to foster better student engagement and improve learning outcomes